OUTDOOR LEARNING MODEL TO DEVELP CREATIVE THINKING ABILITY IN WRITING POETRY - Cahyaning Oktaviani; St. Y. Slamet; Hartono Hartono (Universitas Sebelas Maret, 2018)
Writing poetry is a subject taught at the primary school level. Outdoor learning activities require students directly invited to interact with objects that will be used as material for writing poetry, so that the process of writing poetry learning an object will become more clear and more real. Outdoor learning stimulates the creative power and imagination of the students in order to put their ideas, thoughts, and ideas into poetry. In addition, the teaching and learning process will feel more alive and more fun than by doing the teaching and learning process in the classroom